Additional surface-water deficit to meet global universal water accessibility by 2030. (20th October 2021) - Bo, Yan; Zhou, Feng; Zhao, Jianshi; Liu, Junguo; Liu, Jiahong; Ciais, Philippe; Chang, Jinfeng; Chen, Lei
Abstract: Universal access to safe drinking water for all is a key target of the United Nations Sustainable Development Goal 6. However, how water accessibility improvement impacts domestic water demand and surface-water deficit (the quantity of water demand that exceeds surface-water availability) are poorly known due to uncertainty and variability in domestic water use intensities ( WUI dom ). Here, we developed a data-driven model to create global gridded maps of historical and future WUI dom, constrained by 1758 survey-based records spanning 220 administrative units. The results show that water accessibility improvement dominated the growth in WUI dom over the period 1990–2015, particularly in developing and least-developed economies. Achieving universal water accessibility by 2030 may lead to an additional growth in global mean WUI dom by 21.7 L capita −1 day −1 . Additional 88.3 million people, from 14 developing countries and 9 least-developed countries, may move into domestic surface-water deficit. Another 16% of global irrigated areas would be at risk of irrigation surface-water deficit mainly in South Asia, Central Asia, and North Africa. These findings imply the need of spatially flexible set of actions to achieve global universal water accessibility by 2030 without worsening surface-water deficit. Highlights: Data-driven model was developed for projecting domestic water demand. Water accessibility improvement dominated growth in historical water use intensity. Additional 88.3 million people move into surface-water deficit when meeting SDG6.1 Another 16% of irrigated areas move into surface-water deficit when meeting SDG6.1